2015
DOI: 10.1007/s00267-015-0513-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Responsible Hiking Behavior: Results from a Stated Choice Experiment

Abstract: This research examined the determinants of responsible hiking behavior through a lab-based experiment in which two managerial factors believed to influence individuals' behavior (the presentation of an educational message and the method of displaying degraded trail conditions) were varied across four experimental treatments in a 2 × 2 between subjects factorial design. The effect of trail degradation type (muddiness and erosion) and severity (moderate or severe) of trail degradation were also examined within e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
1
14
1
Order By: Relevance
“…Unlike some other research where signage did not lead to desired behaviors ( Goh, 2020 ; Guo et al, 2015 ), this data revealed a positive association between sign presence and physical-distancing compliance. This finding supports past research where visitors adhere to clearly communicated rules, especially when reinforced by social norms ( Schneider et al, ; Schneider & Hammitt, 1995 ).…”
Section: Discussioncontrasting
confidence: 98%
“…Unlike some other research where signage did not lead to desired behaviors ( Goh, 2020 ; Guo et al, 2015 ), this data revealed a positive association between sign presence and physical-distancing compliance. This finding supports past research where visitors adhere to clearly communicated rules, especially when reinforced by social norms ( Schneider et al, ; Schneider & Hammitt, 1995 ).…”
Section: Discussioncontrasting
confidence: 98%
“…Ecotourism is one outgrowth of the environmental movement and has been defined by the International Union for Conservation of Nature as responsible travel to relatively undisturbed natural areas of the world to enjoy nature, promote conservation, and provide economic benefit for the host community. Several studies have demonstrated negative impact on the environment from recreational activities associated with ecotourism such as the effects of: 1) diving on coral reefs (Santos et al 2015;Giglio et al 2016;Roche et al 2016); 2) hiking on trailside plants (Guo et al 2015); and 3) beachside driving on shorebirds (Weston et al 2014). Such studies are insightful and important because proponents of ecotourism are often unaware about the possibility of environmental harm from ecotourism activities or they proceed under the impression that their activities are environmentally harmless (Wall 1997;Priskin 2003;Weston et al 2014;Giglio et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical disturbances as a result of agricultural runoff or industrial waste and physical disturbances from floods, construction projects, and land-use changes have received much attention in the literature [1] [3]. A newer body of literature has begun to evaluate the influence of disturbance caused by human recreational activity within natural areas on the biota [4] [5] [6] [7] [8]. In addition to considering the disturbance impacts of ecotourism and outdoor recreation, it is important to recognize that outdoor education programs may also cause disturbance to the biota.…”
Section: Introductionmentioning
confidence: 99%